Epilepsy related burn injuries in developing country: An experience in National Burn Hospital. Issue 3 (July 2019) - Lam, Nguyen Nhu; Duc, Ngo Minh; Nam, Le
Highlights: Epileptic patients accounted for 1.38% total burn admission and most of them are living in rural area. Main causal agent was flame or contacting to hot surface during seizures. High rate of full thickness burn injury with more surgeries and longer hospitalization as compared to non-epileptic patients. Patients and health professionals need to be aware of such injuries and appropriate prevention strategies. Abstract: Objectives: Investigating characteristics and outcome of epileptic related burn injuries. Methods: A retrospective study was conducted on all burn patients admitted to the National Burn Hospital during three year period (1/1/2016 to 31/12/2018). Patients were divided into two groups including epilepsy group with 137 patients and non-epilepsy group (9809 patients). Recorded criteria included patients' demographics, burn and epilepsy features relating to burn injuries and treatment outcomes. Results: Epileptic patients accounted for 1.38% total burn admission. More proportion of adult (81.75% vs. 51.09%; p < 0.001) and flame burn (58.39% vs. 41.38%; p < 0.001) were seen in epilepsy group. In addiction, more epileptic patient lived in rural area (79.56% vs. 67.66%; p < 0.01). There was not significant difference in gender and season of burns between two groups. Most burn accidents among epileptic patient occurred during cooking time or contacting to heater (87.60%). All epilepsy related burns occurred during the seizures and 3.65% of them was second burn injuries. In addition, 79.56% of epileptic patients suffered full thickness injury compared to 44.32% among non-epileptic patients (p < 0.001). Full thickness burn area was also remarkably higher (5.38% vs. 3.08%; P = 0.003) among epileptic patients. There was no difference of inhalation injury and co-trauma incidence between two groups (P > 0.05). Higher surgical number (2.35 vs. 1.03; p < 0.01) and longer hospitalization (22.17 vs. 16.44 days; p < 0.001) were recorded in epileptic group. No significant difference was recorded between two groups in term of complication and mortality rate. Conclusion: Epileptic related burn is still public health issue in developing countries with critical burden due to deep burn injuries and prolong hospitalization. Patients and health professionals need to be aware of such injuries and appropriate prevention strategies.